(untitled) (Research, Society and Development, 2023)
We currently have a configuration of university entrants made up of a generation that has access to information through a wide variety of tools. In this sense, it is necessary for schools and universities to seek strategies to monitor, understand and create teaching methodologies that adapt to these new times, thus placing students in an active and participatory position in their learning process. Among these methodologies, we can highlight project-based learning as it is an active teaching methodology that proposes, through the investigation of a central theme, that students can unite theory and practice in a way that each individual involved in the teaching-learning process can articulate in a differentiated way. This study aims to analyze if project-based learning and its relevance for the curricularization of research at the Federal Institute of Education, Science and Technology of Rondônia and to describe the perception and feelings of the students of a discipline of the degree course in chemistry about this methodology and if its application in the discipline of instrumental analysis contributed in some way to their learning. This study was applied in a class of instrumental analysis, a discipline of the degree course in chemistry in which the students elaborated a research project where they chose which parameters to analyze and which methods to use for this and in the end presented the results obtained in the form of a seminar. To verify the perceptions about the methodology, a questionnaire was used that was analyzed from a qualitative perspective. From the results obtained through this questionnaire, we can conclude that yes, this methodology had a positive result because, even considering the time to carry out the activities less than necessary, they consider that the project brought them knowledge that will be useful in the future, especially for those who expressed the desire to follow an academic career focused on scientific research.